Outcome of Gartland Type III Paediatric Supracondylar Humerus Fracture Fixation with the Kapandji Technique in the Prone Position (Medicine Today, 2025)
Introduction with Objective: The aim of the present study was to evaluate the Outcome of Gartland Type III Paediatric Supracondylar Humerus Fracture Fixation with the Kapandji Technique in the Prone Position. Materials and Methods: This prospective study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chittagong within the defined period from January 2020 to February 2022. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. The results were expressed as percentage and mean ± SD and p